The Potential of Isolation Source to Predict Colonization in Avian Hosts: A Case Study in Campylobacter jejuni Strains From Three Bird Species - Atterby, Clara; Mourkas, Evangelos; Méric, Guillaume; Pascoe, Ben; Wang, Helen; Waldenström, Jonas; Sheppard, Samuel K.; Olsen, Björn; Järhult, Josef D.; Ellström, Patrik (Frontiers in Microbiology, 2018)
Campylobacter jejuni is the primary cause of bacterial gastroenteritis worldwide, infecting humans mostly through consumption of contaminated poultry. C. jejuni is common in the gut of wild birds, and shows distinct strain-specific association to particular bird species. This contrasts with farm animals, in which several genotypes co-exist. It is unclear if the barriers restricting transmission between host species of such specialist strains are related to environmental factors such as contact between host species, bacterial survival in the environment etc. or rather to strain specific adaptation to the intestinal environment of specific hosts. We compared colonization dynamics in vivo between two host-specific C. jejuni from a song thrush (ST-1304 complex) and a mallard (ST-995), and a generalist strain from chicken (ST-21 complex) in a wild host, the mallard (Anas platyrhynchos). In 18-days infection experiments, the song thrush strain showed only weak colonization and was cleared from all birds after 10 days, whereas both mallard and chicken strains remained stable. When the chicken strain was given 4 days prior to co-infection of the same birds with a mallard strain, it was rapidly outcompeted by the latter. In contrast, when the mallard strain was given 4 days prior to co-infection with the chicken strain, the mallard strain remained and expansion of the chicken strain was delayed. Our results suggest strain-specific differences in the ability of C. jejuni to colonize mallards, likely associated with host origin. This difference might explain observed host association patterns in C. jejuni from wild birds.